A rudimentary computational assessment of low tip speed ratio asymmetrical wind turbine blades - Naidu Sanderasagran, Ashwindran; Azizuddin, Abd Aziz; Oumer, A. N. (Penerbit UTHM, 2020)
This paper presents a computational study of novel drag type vertical axis wind turbine inspired by three design elements from nature. The aim of this study is to analyze the aerodynamic performance of the proposed design. The design is simulated in FLUENT using SST k-Ï‰ transport model via URANS turbulent model. The model is simulated in 2D in order to save computational time. The design is simulated under the influence of freestream velocity of Uâˆž=8m/s at multiple tip speed ratios. The proposed wind turbine is composed of drag induced novel cavity vane turbine blade for energy capturing. The proposed wind turbine generated low power coefficient, Cp = 0.029 and Cp=0.025 at Î»=0.2 and Î»=0.3 respectively. tip speed ratio Î»=0.4, Î»=0.6 and Î»=0.9 indicated high instability in moment generation and high negative power extraction. Computational result indicated that the geometry of the cavity vane has impacted the performance of the turbine due to its sharp-edged corner. the proposed geometry resulted in unstable moment generation and torque deliverance which impacted the power extraction. The lack of symmetrical and streamline properties of the blades has affected one another as in terms of rotation. The cavity vane experiences high adverse pressure due to its sharp cornered geometry in returning blade which consequently impacted the rotation of the advancing blade.